2022
DOI: 10.1021/acssuschemeng.2c04045
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Influence of Betaine-Based Natural Deep Eutectic Systems on Horseradish Peroxidase

Abstract: To validate the use of horseradish peroxidase (HRP) in natural deep eutectic systems (NADES), five different betaine-based NADES were characterized in terms of water content, water activity, density, and viscosity experimentally and by thermodynamic modeling. The results show that the NADES under study have a water activity of about 0.4 at 37 °C for water contents between 14 and 22 wt %. The densities of the studied NADES had values between 1.2 and 1.3 g.cm–3 at 20 °C. The density was modeled with a state-of-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 69 publications
2
43
0
Order By: Relevance
“…54,55 Previous work has also been explored to evaluate the stability of proteins like keratin, horseradish peroxidase, and laccase in the activity and oligomerization of rutin, a-chymotrypsin in [Ch]Cl-urea and [Ch]Cl-Gly DESs, which concluded that the stability of the proteins was conserved in both DESs. 26,48,[56][57][58] Esquembre et al 59 have demonstrated that [Ch]Cl-urea caused destabilization of the lysozyme, whereas [Ch]Cl-Gly provided stability to the protein, and similar results for[Ch]Cl-Gly have been provided by Fernandez et al 26 as the structure of the lysozyme was retained at higher concentrations in the presence of [Ch]Cl-Gly. On the other hand, Monhemi proved that [Ch]Cl-urea provided good conformational stability to lipase.…”
Section: Thermodynamic Analysis Of Hb In the Presence Of Dessmentioning
confidence: 80%
“…54,55 Previous work has also been explored to evaluate the stability of proteins like keratin, horseradish peroxidase, and laccase in the activity and oligomerization of rutin, a-chymotrypsin in [Ch]Cl-urea and [Ch]Cl-Gly DESs, which concluded that the stability of the proteins was conserved in both DESs. 26,48,[56][57][58] Esquembre et al 59 have demonstrated that [Ch]Cl-urea caused destabilization of the lysozyme, whereas [Ch]Cl-Gly provided stability to the protein, and similar results for[Ch]Cl-Gly have been provided by Fernandez et al 26 as the structure of the lysozyme was retained at higher concentrations in the presence of [Ch]Cl-Gly. On the other hand, Monhemi proved that [Ch]Cl-urea provided good conformational stability to lipase.…”
Section: Thermodynamic Analysis Of Hb In the Presence Of Dessmentioning
confidence: 80%
“…The DES prepared in this work have been designed for the evaluation of their potential as enzyme stabilizing agents (Gajardo-Parra et al 2022 ). Their use in a large industrial scale requires their full characterization not only in terms of their physico-chemical properties, but also their ecotoxicological profile.…”
Section: Resultsmentioning
confidence: 99%
“…Their use in a large industrial scale requires their full characterization not only in terms of their physico-chemical properties, but also their ecotoxicological profile. The physico-chemical characterization is presented in a previous paper (Gajardo-Parra et al 2022 ), and hence here we focus mostly on their toxicity profile.…”
Section: Resultsmentioning
confidence: 99%
“…Throughout this work, the enzymatic activity of HRP was assessed as described elsewhere. 34 2.4. Evaluation of HRP activity and thermostability in NADES Enzyme activity of HRP was tested upon incubation in NADES for 6 h and 24 h at 37 ⁰C.…”
Section: Enzymatic Activity Assaymentioning
confidence: 99%
“…DES or IL), thinking about the final application, which significantly reduces the dependence on a great experimental effort. In a previous work from this group, 34 several betaine-based NADES were fully characterized in terms of water content and activity, viscosity and density. Moreover, the influence of these NADES in the activity and structure of HRP was also accessed.…”
Section: Introductionmentioning
confidence: 99%